PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN KINEMASTER APLICATION PADA KURIKULUM MERDEKA UNTUK KELAS IV SD - Estuhono, Estuhono; Sapitri, Sindi (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The background of this research is the low learning outcomes of students in class IV SD, especially in science subjects, which is caused by the teacher not having teaching materials such as learning videos so that the learning process only takes place using the teacher's book and student's book. The purpose of this research is to produce learning video media that is valid, practical and effective. This research is a development research using the ADDIE model. This research was conducted in several stages, namely Analyze, Design, Development, Implementation, Evaluation. The results of validation research by three validators have an average score of 87 with a very valid category. The results of research on the practicality of learning videos conducted by teachers and students in grade IV SD have an average score of 95.5 in the very practical category. The effectiveness results carried out by all fourth grade elementary school students obtained a passing percentage of 93.1 in the very effective category. So, the conclusion of this study is that the development of learning videos using the Kinemaster Application has valid, practical, and effective criteria.